Identification of a novel major QTL and F-box candidate genes controlling seed dormancy in common wheat - Yuxia Lyu; Yaoyao Zhao; Wenbo Lu; Xu Pan; Wei Gao; Litian Zhang; Huanfeng Wang; Zhaoyu Yu; Ruihan Wang; Tingfeng Shou; Bingbing Tian; Jiajia Cao; et al. (Theoretical and Applied Genetics, 2026)

Uranium release from iron-rich acid soils under IPCC elevated CO2 scenarios: One-sided organic nanocolloidal dominance rather than expected iron oxide colloids - Ziyan Wang; Tingfeng Cheng; Caiqin Wang; Yuwei Zhao; Daoyong Zhang; Xiangliang Pan (Journal of Hazardous Materials, 2025)

Mechanism and kinetics of microwave-enhanced disposal of Zn-bearing dust using petroleum coke - Haiming Cheng; Zhuo Chen; Tingfeng Yao; Guangqiang Pu; Dianchun Ju; Weitong Du (Journal of Environmental Chemical Engineering, 2025)

Piezoelectric polarization modulates photocarrier kinetics via enhanced built-in field at heterojunctions - Jiliang Niu; Tingfeng He; Cheng Qiu; Zhengguo Song (Chemical Engineering Journal, 2025)

Fast and Deterministic Underwater Point Cloud Registration for Multibeam Echo Sounder Data - Liang Zhao; Lan Cheng; Tingfeng Tan; Chun Cao; Feihu Zhang (Journal of Marine Science and Engineering, 2024)
Investigating underwater environments using Multi-Beam Echo Sounder (MBES) point cloud registration technology is a critical yet underdeveloped area in oceanographic research. This paper presents a fast, deterministic Branch-and-Bound (BnB) method with four degrees of freedom, which combines Inertial Measurement Unit (IMU) data with MBES point cloud data for precise registration. Given the prevalence of outliers and noise in underwater acoustic measurements, the BnB method is employed to provide globally deterministic solutions. However, due to the exponential convergence speed of the BnB method with respect to the dimensionality of the solution space, searching within a six-degree-of-freedom parameter space (three rotational and three translational degrees of freedom) can be extremely time-consuming. To this end, the Z-axis of the point cloud is aligned with the gravitational direction of the IMU, reducing the rotational degrees of freedom from three to one, specifically concerning yaw. Additionally, an outlier exclusion strategy is introduced to eliminate mismatches, significantly reducing the number of key-point correspondences and thereby improving registration efficiency. Experiments conducted on both public and real-world lake datasets demonstrate that the proposed method achieves a favorable balance between speed and accuracy, outperforming other tested methods and meeting the demands of contemporary research.

Prototypical basin reconstruction and evolutionary models for the Precambrian of the Qinshui Basin, North China craton - Tianshun Liu; Wenlong Ding; Zhong Liu; Zhijun Li; Pengbao Zhang; Chuanli Peng; Xiaoyun Cheng; Tingfeng Liu; Tong Gou (Marine and Petroleum Geology, 2024)

In-situ synthesis of carbon-coated Co3O4 nanowire for efficient activation of peroxymonosulfate while reducing ion leaching through protection and secondary enrichment - Jiliang Niu; Tingfeng He; Jianhua Cheng (Chemical Engineering Journal, 2024)

Engineering microalgae for robust glycolate biosynthesis: Targeted knockout of hydroxypyruvate reductase 1 combined with optimized culture conditions enhance glycolate production in Chlamydomonas reinhardtii - Suihao Yan; Yuyong Hou; Meijie Cui; Tingfeng Cheng; Sihan Lu; Zhiyong Liu; Bicheng Deng; Weijia Liu; Menglin Shi; Liangcai Lin; Longjiang Yu; Lei Zhao (Bioresource Technology, 2024)

Side-Scan Sonar Image Generator Based on Diffusion Models for Autonomous Underwater Vehicles - Feihu Zhang; Xujia Hou; Zewen Wang; Chensheng Cheng; Tingfeng Tan (Journal of Marine Science and Engineering, 2024)
In the field of underwater perception and detection, side-scan sonar (SSS) plays an indispensable role. However, the imaging mechanism of SSS results in slow information acquisition and high complexity, significantly hindering the advancement of downstream data-driven applications. To address this challenge, we designed an SSS image generator based on diffusion models. We developed a data collection system based on Autonomous Underwater Vehicles (AUVs) to achieve stable and rich data collection. For the process of converting acoustic signals into image signals, we established an image compensation method based on nonlinear gain enhancement to ensure the reliability of remote signals. On this basis, we developed the first controllable category SSS image generation algorithm, which can generate specified data for five categories, demonstrating outstanding performance in terms of the Fréchet Inception Distance (FID) and the Inception Score (IS). We further evaluated our image generator in the task of SSS object detection, and our cross-validation experiments showed that the generated images contributed to an average accuracy improvement of approximately 10% in object detection. The experimental results validate the effectiveness of the proposed SSS image generator in generating highly similar sonar images and enhancing detection accuracy, effectively addressing the issue of data scarcity.

Lake shrinkage–induced terrestrial ecological environmental quality degradation in a semiarid lake basin - Nannan Cheng; Tengteng Yang; Tingfeng Wu; Runtao Hu; Xiangyu He (Environmental Science and Pollution Research, 2023)

Alkalization-induced disintegration increased redox activity of solid humic acids and its soil biogeochemical implications - Caiqin Wang; Shuting Tang; Hangzhe Chen; Tingfeng Cheng; Daoyong Zhang; Xiangliang Pan (Science of The Total Environment, 2023)

Electrochemical properties of humic acid and its novel applications: A tip of the iceberg - Caiqin Wang; Tingfeng Cheng; Daoyong Zhang; Xiangliang Pan (Science of The Total Environment, 2023)

Protective-mechanism-exclusive thermal stability modes of soil organic matter: Novel implication for wildfire effect on soil organic carbon - Caiqin Wang; Tingfeng Cheng; Shuting Tang; Mengxuan Li; Daoyong Zhang; Xiangliang Pan (Science of The Total Environment, 2023)

Affinity-based alleviation of dissolved organic matter (DOM) on tetracycline toxicity to photosynthesis of green algae Chlorella vulgaris: roles of hydrophilic and hydrophobic DOM - Caiqin Wang; Hang Xu; Tingfeng Cheng; Shuting Tang; Daoyong Zhang; Meichao Li; Xiangliang Pan (Environmental Science and Pollution Research, 2023)